The Conceptual Metaphor Analysis in the Song Lyrics “Is You” by Jay Chang (2020) - Fadhila, Naura; Juanda, Juanda (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
The objective of this study research is to investigate the manner in which metaphors are communicated in song lyrics through the application of conceptual metaphor theory, which consists of source and target data and aims to clarify how abstract concepts are conceptualized and comprehended. By employing a descriptive qualitative research method and conceptual theory, this study achieves coherent and systematic findings. The data used is a song from Jay Chang entitled